Between Tradition and Innovation: Religious Practices and Everyday Life of Second-Generation Muslim Women. (1st December 2016) - Acocella, Ivana; Cataldi, Silvia; Cigliuti, Katia
Abstract : The article focuses on the identity construction and recognition strategies adopted by young second-generation Muslim women living in Italy. The research was conducted by collecting life stories with the goal of investigating the processes of identity building in the private and in the public sphere. Moving from two key concepts, agency and intersectionality, the study explores those challenges and tensions which arise from the multi-membership (intra-ethnic and inter-ethnic; intra-generational and inter-generational) and from the interconnection of different social categories (gender, religious beliefs, age and ethnic origins) of young Muslim females. At the end of the study, the biographies are analysed inductively in order to identify different ideal-types of profiles of subjectification which vehiculate different gender and religious identity patterns.